Effect of the Feeding of Formula Milk Enriched with Pro-Antioxidants for the Prevention of Preeclampsia; Study of High Sensitivity C-Reactive Protein (hs-CRP) and Cell-Free mRNA of Plasminogen Activator Inhibitor-1 (PAI-1) in Plasma - Wibowo, Noroyono (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To evaluate the effect of the feeding of formula milk enriched with pro-antioxidants to high sensitivity C-reactive protein (hs-CRP) and cell-free mRNA of Plasminogen Activator Inhibitor-1 (PAI-1) in the first trimester, second trimester, and post labor for the prevention of preeclampsia. Method: This is double-blinded randomized clinical trial in 8-12 weeks pregnant woman with low (below 900 Î¼mol/l) Ferric Reducing Ability of Plasma (FRAP), as a marker of low systemic antioxidant. A total of 104 samples were collected from patients who had antenatal care in Bunda Hospital Jakarta, Budi Kemuliaan Hospital, and Dr.Cipto Mangunkusumo General Hospital from January 2007 until December 2009. From block randomization, 49 samples were allocated in the case group, and 55 samples to the control group. A formula milk enriched with pro-antioxidants was fed to the case group throughout their pregnancy, and a regular pregnancy formula milk was fed to the control group. Hs-CRP and cell-free mRNA PAI-1 test in the two groups at first trimester, second, and post labour was conducted. The incidence of preeclampsia was then compared in the two groups. Result: Significant difference (p